Keterbukaan Diri Remaja dalam Penggunaan WhatsApp: Studi Sosiologis Tentang Privasi dalam Keluarga - Silvia Maulidia; Yustika Irfani Lindawati (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2026)
This study aims to find out how open adolescents are when using WhatsApp and how this relates to privacy in the family. The methodology used in this study is qualitative with a phenomenological approach to explore the personal experiences of informants. The data was obtained through in-depth interviews with six students aged between 19 and 21 years old from Sultan Ageng Tirtayasa University. The results of this study reveal that adolescents widely use WhatsApp as a tool to communicate, share information, and express feelings through various existing features, such as private messages and statuses. Nonetheless, they also tend to be selective in sharing certain information, especially to parents, to maintain their personal privacy. Some informants choose to use privacy features, such as hiding their status from parents, to avoid misunderstandings or potential conflicts within the family. Although WhatsApp helps maintain the relationship between teens and their families, privacy-related tensions persist due to differences in understanding between teens and parents about the use of digital media. These findings show that digital privacy management is an adaptive strategy carried out by adolescents to maintain a balance between self-openness and harmonious family relationships in the era of digital communication.